Relationship Between Post-exercise Heart Rate Recovery and Changing Ratio of Cardiopulmonary Exercise Capacity - Kim, Ji-Hyun (Ann Rehabil Med, 2017)
OBJECTIVE: To determine whether heart rate recovery (HRR) following an exercise tolerance test (ETT) is correlated with a changing ratio of peak oxygen consumption (VO(2)) and maximal metabolic equivalents (MET(max)). METHODS: A total of 60 acute myocardial infarction (AMI) patients who underwent ETT at both assessment points - 3 weeks (T0) after the AMI attack and 3 months after T0 (T1) were included. After achieving a peak workload, the treadmill was stopped with a 5-minute cooldown period, and the patients recovered in a comfortable and relaxed seated position. HRR was defined as the difference between the maximal heart rate (HR(max)) and the HR measured at specific time intervals - immediately after the cool down period (HRR-0) and 3 minutes after the completion of the ETT (HRR-3). RESULTS: HRR-0 and HRR-3 increased over time, whereas VO(2max) and MET(max) did not show significant changes. There was a positive correlation between HRR at T0 and the exercise capacity at T0. HRR at T0 also showed a positive correlation with the exercise capacity at T1. There was no significant correlation between HRR measured at T0 and the change in the ratio of VO(2max) and MET(max), as calculated by subtracting VO(2max) and MET(max) obtained at T0 from those obtained at T1, divided by VO(2max) at T0 and multiplied by 100. CONCLUSION: Post-exercise HRR measured at 3 weeks after the AMI onset can reflect the exercise capacity 3 months after the first ETT. However, it may be difficult to correlate post-exercise HRR at T0 with the degree of increase in cardiopulmonary exercise capacity in patients with AMI.